How to promote cycling. Life Cycle implementation manual. 3rd Edition. - Köllinger, Claus; Rzewnicki, Randy; Fismer, Raymond (My University, 2011)
The manual is a collection of successful concepts which have been tested across Europe by the ten organisations collaborating in the LIFE CYCLE project. Complete with guidelines on how, where, when and with whom to adapt and implement similar projects, the manual is a toolbox of practical solutions for organisations seeking to stimulate cycling in our society.
Keywords: Individualverkehr; Fahrradverkehr; Handlungsempfehlung; Fahrradförderung; Best Practice; Mobilitätsförderung; Mobilitätsverhalten; Handbuch